Butyrolactone‐I, an efficient α‐glucosidase inhibitor, improves type 2 diabetes with potent TNF‐α–lowering properties through modulating gut microbiota in db/db mice. Issue 11 (26th August 2019) - Wu, Wei; Liu, Liyun; Zhu, Hongrui; Sun, Yating; Wu, Ying; Liao, Hongze; Gui, Yuhan; Li, Lei; Liu, Lei; Sun, Fan; Lin, Houwen
Abstract : The aim of this study was to evaluate the effects of butyrolactone‐I (A6) on type 2 diabetes (T2D) in db/db mice because A6 was found to inhibit α‐glucosidase activities and TNF‐α release, which were associated with improving T2D. Male db/db mice were divided into 6 groups and given an equivalent volume of olive oil, acarbose, or different doses of A6 for 4 wk ( n = 8/group). In this study, 11 butenolide derivatives were screened for their α‐glucosidase and TNF‐α suppressive activity in vitro . A6, an efficient α‐glucosidase inhibitor, exerts hypoglycemic and multiple activities in reducing weight, improving glucose tolerance and insulin resistance, increasing short‐chain fatty acid (SCFA) levels, activating SCFA‐induced increases in glucagon‐like peptide 1 and peroxisome proliferator‐activated receptor‐γ expression, enhancing intestinal mucosal barrier function and mitigating endoxemia in db/db mice. These effects may result from mediation of gut microbiota by A6. Meanwhile, A6, with potent TNF‐α–lowering properties, was demonstrated to have multiple salutary effects with excellent structural stability and long‐term safety in vivo . A6, an effective α‐glucosidase inhibitor with high security and stability, exerted potent antidiabetic effects in vivo . Furthermore, the modulation of gut microbiota of A6 was demonstrated to be one of the mechanisms contributing to anti‐inflammation properties and improving endoxemia. Our work confirms that the compound A6 is a prospective drug candidate for T2D.—Wu, W., Liu, L., Zhu, H., Sun, Y., Wu, Y., Liao, H., Gui, Y., Li, L., Liu, L., Sun, F., Lin, H. Butyrolactone‐I, an efficient α‐glucosidase inhibitor, improves type 2 diabetes with potent TNF‐α–lowering properties through modulating gut microbiota in db/db mice. FASEB J. 33, 12616–12629 (2019). www.fasebj.org